PENINGKATAN PENGETAHUAN IBU-IBU PKK DI DESA BULANG DALAM PENGOLAHAN JAHE BUBUK INSTAN SEBAGAI ISIAN KLEPON - ., Mulyono (Jurnal Abadimas Adi Buana, 2017)
Bulang village is one Prambon One village in the district, Sidoarjo regency. Some businesses Namely society has many souvenir shops Typical klepon Bulang village. Activities that can be done to review increasing knowledge PKK is pengolahaan TOGA And to Adding innovation and creativity as the Biodiversity Variation cake klepon to review the utilization of the findings of Plant TOGA Namely ginger instant powder for a review to inform as increase knowledge shown to the PKK , Its activities KKN PPM method used is Demonstrations Namely deliver material and practice. Target Success junlah Trainees can be said to be Good. Training goal achievement can be said to be good. There is an increased knowledge of participants about Processing From the instant powdered ginger as stuffing klepon. Target Achievement Yang has planned material can be said to be very good. Participants ability hearts penguasan Good material. Submission of materials with Demonstration And Also Participants Participate practice.